Paylater System and People's Consumptive Behavior: A Phenomenological Study - Ni Putu Yoni Widiasih; Ayudia Sokarina; Isnawati, Isnawati (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
The development of e-commerce in Indonesia has changed the payment method, which originally used cash, but now it is starting to be introduced with an electronic-based payment system. One type of payment method is paylater. The use of paylater is estimated to be one of the causes of increased purchasing power. The purpose of the research is to interpret the consumptive behavior caused by the paylater system. This research is a qualitative research with a phenomenological approach. The data collection techniques in this research are interviews and documentation. The informants in this study are active users of the paylater payment method such as students, private employees, and security guards. The results of this study show that the paylater payment method triggers consumptive behavior because of the various conveniences provided. This is inseparable from the demands of the contemporary lifestyle followed by the informants.